Histologic margins and the residual tumour classification scheme: Is it time to use a validated scheme in human oncology to standardise margin assessment in veterinary oncology?. (6th December 2019) - Liptak, Julius M.
Abstract: There is no consensus on the definition of a complete histologic excision in veterinary oncology; many definitions have been used in various studies, but these have been arbitrarily selected with no apparent justification. The residual tumour classification scheme, where a complete histologic excision is defined as a histologic tumour‐free margin >0 mm, has been used for >40 years in human oncology by all of the major clinical staging organizations and is considered highly prognostic for the vast majority of malignant tumours in people. Because of the widespread use of the residual tumour classification scheme both clinically and in research studies, this standardized approach permits better communication between clinicians, an evidence‐based decision‐making process for adjuvant treatment options following surgical resection, minimizes exposing patients to unnecessary adjuvant treatments and a better ability to compare local tumour control for specific tumours between different studies. The adoption of the residual tumour classification scheme in veterinary oncology would likely achieve similar outcomes and minimize the prevalent confusion within the veterinary community, amongst both general practitioners and specialists, regarding the definition of what constitutes a complete histologic excision.